Silicon envy: How global innovation clusters hurt or stimulate each other across developed and emerging markets - Harmancioglu, Nukhet; Tellis, Gerard J (Journal of International Business Studies, 2018)
The authors examine intercluster dynamics among rival global clusters on monthly counts of patents, startups, and new product commercializations between 1999 and 2014 while controlling for numerous exogenous variables. Results show that rival innovation clusters facilitate rather than hinder each other’s growth due to resources complementarities. Reverse fertilization occurs from emerging to developed clusters, contrary to the received wisdom. This study is the first to show intercluster dynamics as important drivers of cluster growth. To explain the counterintuitive findings, the authors draw upon the coopetition view which suggests mutually beneficial growth across all rival clusters rather than zero-sum gains.